Non-Abelian strings in N = 1 supersymmetric QCD * - Ievlev Evgenii; Yung Alexei (EPJ Web of Conferences, 2018)
Non-Abelian flux tubes (strings) are well studied in N = 2 supersymmetric QCD in (3+1) dimensions. In addition to translational zero modes they have also orientational moduli associated with rotations of their fluxes inside a non- Abelian group. The dynamics of the orientational moduli is described by the two dimensional CP(N - 1) model living on the world sheet of the non-Abelian string. In this paper we consider a deformation of N = 2 supersymmetric QCD with the U(N) gauge group and Nf = N quark flavors with a mass term μ of the adjoint matter. In the limit of large μ the theory flows to an N = 1 supersymmetric QCD. We study the solution for the non-Abelian string in this limit and derive an effective theory on the string world sheet. The bosonic sector of this theory is still given by the CP(N -1) model. We study also the fermionic sector of the world sheet theory. Upon the deformation the non-Abelian string is no longer BPS and we show that the fermionic superorientational zero modes are all lifted. This leaves us with the pure bosonic CP(N-1) model on the string world sheet in the limit of N = 1 QCD. We discuss what happens to confined monopoles at large μ.